The impact of Government Ownership on Dividend Policy: Case in Viet Nam and Taiwan - Hang Thi Thuy Pham; Jung-Sung Chang (My University, 2018)
The impact of Government Ownership on Dividend Policy: Case in Viet Nam and Taiwan
Keywords: Government ownership; Dividend policy; Vietnam and Taiwan